THE INFLUENCE OF WORKLOADS AND WORK STRESS ON EMPLOYEE SATISFACTION (Study on Kalsel Bank Main Branch Banjarmasin) - Puteri, Isni Andini (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to determine how the effect of workload and job stress on employee job satisfaction at the Bank Kalsel Main Branch in Banjarmasin City. This type of research is explanatory research which explains or proves the relationship or influence between the independent and dependent variables. This study used a sample of 120 respondents in which the distribution of questionnaires was carried out in the main branch of South Kalimantan Bank in Banjarmasin City. Sampling using a non-probability sampling method with a purposive sampling technique. The sample consisted of respondents with permanent employees with a minimum service period of two years at the Bank Kalsel Banjarmasin Main Branch in Banjarmasin City. Data analysis used multiple linear regression analysis using SPSS ver. 21. The results showed that of the two variables, namely workload and work stress, both of them had a significant negative effect on employee job satisfaction.Keywords: workloads, work stress, employee job satisfaction